Posted by **Hannah** on Monday, November 8, 2010 at 8:55pm.

Show that (f X g)(x) = (g X f)(x) = x for f(x)= 3x-5 and g(x)= x+5 / 3

I have know idea how to do this.

## Answer This Question

## Related Questions

- English - Hi for my english class, we have to make an invention using cheap ...
- math - F(x)=9x^3+2x^2-5x+4 and g(x)=5x^3-7x+4. What is f(x)-g(x)? Show all of ...
- 7th grade math Ms. Sue please help I have no idea! - #10 On a blueprint, 1 inch...
- English - Hi for my english class, we have to make an invention using cheap ...
- Algebra - 17-Identify the vertex, axis of symmetry and x-intercept(s) of F(x)=(x...
- the big idea of energy - i have to do an assesment about sound. i have to ...
- math - Show that the sum of the squares of any five consecutive integers is ...
- INTEGRAL CALCULUS PLEASE HELP!!! - If F(x)dx=1 from 1 to 25, F(x)dx=4 from 1 to ...
- Algebra - If (x+2)² = 25 and x > 0, what is the value of x? I have no idea ...
- Math - A tuition bill was $4360. If she paid $6052 what's the percentage ...

More Related Questions